A Research on the Selection of Suitable Regional Intermediate Transformer Station Location - Dang , Quang Khoa (Journal of Technical Education Science, 2021)
Many writers have proposed a method of defining substation location according to the load centre. This paper focuses on analyzing, describing and supplementing the method of load centralization to overcome the problems that are not solved by the additional charge method. Through it, this paper also studies the choice of location for the regional intermediary transformer station conforming to the Scheme of Electrical Network to reduce power loss.